A novel strategy for screening new natural products by a combination of reversed-phase liquid chromatography fractionation and 13C NMR pattern recognition: the discovery of new anti-cancer flavone dimers from Dysosma versipellis (Hance)1. Issue 95 (15th October 2015) - Yang, Zhi; Wu, Youqian; Zhou, Hui; Cao, Xiaoji; Jiang, Xinhang; Wang, Kuiwu; Wu, Shihua
<x xml:space="preserve">Abstract</x> A new screening strategy for the discovery of new natural products by a combination of reversed-phase liquid chromatography (RPLC) and 13C NMR pattern recognition.